Celiac Disease and Pediatric Type 1 Diabetes: Diagnostic and Treatment Dilemmas. (10th May 2010) - Sud, Shama; Marcon, Margaret; Assor, Esther; Palmert, Mark R.; Daneman, Denis; Mahmud, Farid H.
Abstract : Despite the advent of sensitive and specific serologic testing, routine screening for celiac disease (CD) in diabetic populations may not be universal practice, and many clinicians struggle to find the optimal approach to managing CD in pediatric Type 1 diabetes (T1D) patients. While some clinicians advocate screening for CD in all patients with T1D, others are unsure whether this is warranted. The diagnosis of patients who present with symptomatic CD, including malabsorption and obvious pathology upon biopsy, remains straightforward, with improvements noted on a gluten-free diet. Many patients identified by screening, however, tend to be asymptomatic. Evidence is inconclusive as to whether the benefits of screening and potentially treating asymptomatic individuals outweigh the harms of managing a population already burdened with a serious illness. This review focuses on current knowledge of CD in children and youth with T1D, highlighting important elements of the disease's pathophysiology, epidemiology, clinical presentation, and diagnostic challenges.